2019
DOI: 10.1101/843060
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduction of cybersickness during and immediately following noisy galvanic vestibular stimulation

Abstract: The mechanism underlying cybersickness during virtual reality (VR) exposure is still poorly understood, although research has highlighted a causal role for visual-vestibular sensory conflict. Recently established methods for reducing cybersickness include galvanic vestibular stimulation (GVS) to mimic absent vestibular cues in VR, or vibration of the vestibular organs to add noise to the sensory modality. Here, we examined if applying noise to the vestibular system using noisy-current GVS also affects sickness… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In related visual-vestibular sensory integration research, Lepecq et al have shown that perceived self-motion trajectory can be altered when a visual display is presented simultaneously with GVS that induces the perception of tilting compared to a visual-only control condition (Lepecq et al, 2006). Generally, visual vection takes several seconds to experience, however, research by some researchers has shown that visual vection latency can be reduced when noisy GVS (i.e., GVS signaling motion in no particular direction) is administered while viewing a visual display signaling vection (Weech, 2017;Weech & Troje, 2017). Additionally, Weech, Varghese, and Barnett-Cowan, have shown that visual vection is stronger with the use of noisy vestibular signals (Weech et al, 2018).…”
Section: Discussion Of Experiments 2 Results and Comparisons To Exper...mentioning
confidence: 99%
“…In related visual-vestibular sensory integration research, Lepecq et al have shown that perceived self-motion trajectory can be altered when a visual display is presented simultaneously with GVS that induces the perception of tilting compared to a visual-only control condition (Lepecq et al, 2006). Generally, visual vection takes several seconds to experience, however, research by some researchers has shown that visual vection latency can be reduced when noisy GVS (i.e., GVS signaling motion in no particular direction) is administered while viewing a visual display signaling vection (Weech, 2017;Weech & Troje, 2017). Additionally, Weech, Varghese, and Barnett-Cowan, have shown that visual vection is stronger with the use of noisy vestibular signals (Weech et al, 2018).…”
Section: Discussion Of Experiments 2 Results and Comparisons To Exper...mentioning
confidence: 99%